Does Firm Size Moderating Influence Of Sales Growth On Tax Avoidance ? - Nor Rahma Rizka; Rika Meidiana Rahayu (Universitas Serang Raya, 2023)
This study aims to obtain empirical evidence concerning the effect of sales growth and firm size on tax avoidance and to empirically prove whether firm size can moderate the effect between sales growth and tax avoidance. This study was conducted on mining companies listed on the Indonesia Stock Exchange from 2014 to 2019. This study involved 17 companies with a total of 102 observations. Data were analyzed using moderated regression analysis. The results showed that sales growth and firm size had a positive effect on tax avoidance. Besides, firm size strengthened the effect of sales growth on tax avoidance.